2023
DOI: 10.3390/cells12081156
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and Breast Cancer: Connected in Growth, Progression, and Therapy

Abstract: Despite an increase in the incidence of breast cancer worldwide, overall prognosis has been consistently improving owing to the development of multiple targeted therapies and novel combination regimens including endocrine therapies, aromatase inhibitors, Her2-targeted therapies, and cdk4/6 inhibitors. Immunotherapy is also being actively examined for some breast cancer subtypes. This overall positive outlook is marred by the development of resistance or reduced efficacy of the drug combinations, but the underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 297 publications
0
7
0
1
Order By: Relevance
“…Autophagy has been reported to be closely correlated with the malignant transformation of cancer cells (Onorati et al 2018 ; Li et al 2020 ). Existing study has demonstrated that autophagy may play the multifaceted role in breast cancer tumorigenesis and metastasis (Wu and Sharma 2023 ; Niklaus, et al 2021 ). Notably, PDK4 regulates autophagy to participate in vascular calcification (Ma et al 2020 ) and non-small cell lung cancer (Zhang et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy has been reported to be closely correlated with the malignant transformation of cancer cells (Onorati et al 2018 ; Li et al 2020 ). Existing study has demonstrated that autophagy may play the multifaceted role in breast cancer tumorigenesis and metastasis (Wu and Sharma 2023 ; Niklaus, et al 2021 ). Notably, PDK4 regulates autophagy to participate in vascular calcification (Ma et al 2020 ) and non-small cell lung cancer (Zhang et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…ACD in response to anticancer drugs has been reported, for example, in breast, colon, and ovarian cancer tissues [ 67 , 68 ]. Tamoxifen induces ACD in breast cancer cells in association with Akt downregulation; conversely, autophagy is involved in tamoxifen resistance via the activation of the PI3K/Akt/mammalian target of rapamycin (mTOR) signaling pathway [ 69 ]. Histone deacetylase inhibitors induce mitochondria-mediated apoptosis and caspase-independent ACD in multiple human cancer cell types [ 70 ].…”
Section: Non-apoptotic Cell Deathmentioning
confidence: 99%
“…Current research suggests that autophagy can serve as a form of nutritional support for cellular self-repair. However, it may also contribute to tumor dormancy in breast cancer, potentially promoting chemoresistance and relapse ( 146 , 147 ).…”
Section: Other Forms Of Cell Death and Breast Cancermentioning
confidence: 99%